Comparison between lactate minimum and critical speed throughout childhood and adolescence in swimmers - Mezzaroba, P. V.; Papoti, M.; Machado, F. A. (Pediatric Exercise Science, 2014)
This study aimed to examine the influence of age and degree of maturity on the comparison and relationship between lactate minimum intensity (LM) and critical speed (CS) throughout childhood and adolescence in swimmers. Forty-six male swimmers aged between 10 and 18 years were divided into three age groups accord- ing to pubertal stages and training status. Maximal efforts of 100 and 400 m and the LM protocol with 200 m performances were executed. CS was determined with a 3-distances combination (100, 200, and 400 m). One-way and mixed analysis of variance for repeated measures, Bland-Altman, Pearson correlation, percent- age difference, and effect size were used to compare and examine the relationship between variables in each age group. The results revealed that LM and CS had differences in comparison with one another throughout childhood and adolescence in swimmers, because CS clearly underestimated LM in the 10 to 12.6-year age group, while overestimating it in the 15.4 to 18-year age group of swimmers. Thus, coaches and swimmers must be aware of the age-dependency of CS for indices of aerobic endurance measurements in the initial ages of systematized swimming training.